Color research of rural tourism destination based on chromatographic analysis: A lowland case study of Hangzhou Meijiawu Village - X.M. Zhao; J.W. Lin; Y.X. Lei; Y. Chen; J.R. Shi; Z. Wang; K. Hokao (International Association of Lowland Technology, 2017)
Good color for rural planning not only brings comfortable living environment, creates an impressive image, but also is conducive to the color context of inheritance and to reserve the unique style. At present, there is not much research on rural color planning in rural country, so this paper chose the rural tourism destination, Meijiawu Village, as a case. and it analyzed the color of the village by using qualitative and quantitative methods. On the basis of tourists' perception of Meijiawu colors, this paper proposed several optimization suggestions about the various types of color and material color by extracting the chroma, lightness and saturation information, including the mass-tone attune (building facade, plant color), auxiliary color (the color of roof, doors, windows and other components, facade color), embellishment color (the color of signs, other colors) and 7 class material colors.